Digital Protractor Integration in PhET Simulation for Proving Snell's Law in Mirror Geometric Optics: An Exploratory Study and Measuring Conceptual Understanding - Najmah Nur Kamilah; Siti Wahyuni (Physics Communication, 2025)
Technological developments are driving the transformation of science learning, including physics, from conventional to digital-based approaches. This study examines the use of a digital protractor in PhET simulations to verify Snell's Law (the law of reflection, θ₁ = θ₂) in geometric optics involving mirrors (plane, concave, and convex). This study aims to explore the innovation of digital protractor integration as a tool in PhET simulations on geometric optics, while also examining its implications as a learning aid for prospective physics teachers. This study is motivated by the challenges of abstracting optics material and the demands of STEM implementation in the Merdeka Curriculum. Employing a descriptive qualitative method with 15 physics students, the research found that this integration improves conceptual understanding despite technical issues such as inaccurate protractor placement and normal line errors. Data analysis confirmed Snell’s Law compliance, though success rates varied with procedural complexity. Students praised the dynamic visualization and efficiency but noted limitations, such as over-idealization. The results advocate for a blended learning approach, combining digital tools with traditional lab work to optimize optics education.